The Saturday Night Ghost Club - Davidson, Craig, 1976- (Penguin Books, 2019)
"A short, irresistible, and bittersweet coming-of-age story in the vein of Stranger Things and Stand by Me about a group of misfit kids who spend an unforgettable summer investigating local ghost stories and urban legends"--